Pro-Apoptotic and Anti-Migration Properties of a Thiazoline-Containing Platinum(II) Complex in MDA-MB-231 Breast Cancer Cells: The Role of Melatonin as a Synergistic Agent - Samuel Estirado; Elena Fernández-Delgado; Emilio Viñuelas-Zahínos; Francisco Luna-Giles; Ana B. Rodríguez; José A. Pariente; Javier Espino (MDPI AG, 2022)
Triple-negative breast cancer (TNBC) is an aggressive cancer insensitive to hormonal and human epidermal growth factor receptor 2 (HER2)-targeted therapies and has a poor prognosis. Therefore, there is a need for the development of convenient anticancer strategies for the management of TNBC. In this paper, we evaluate the antitumoral potential of a platinum(II) complex coordinated with the ligand 2-(3,5-diphenylpyrazol-1-yl)-2-thiazoline (DPhPzTn), hereafter PtDPhPzTn, against the TNBC cell line MDA-MB-231, and compared its effect with both cisplatin and its less lipophilic counterpart PtPzTn, the latter containing the ligand 2-(pyrazol-1-yl)-2-thiazoline (PzTn). Then, the putative potentiating actions of melatonin, a naturally occurring antioxidant with renowned antitumor properties, on the tumor-killing ability of PtDPhPzTn were also checked in TNBC cells. Our results show that PtDPhPzTn presented enhanced cytotoxicity compared to both the classical drug cisplatin and PtPzTn. In addition, PtDPhPzTn was able to induce apoptosis, being more selective for MDA-MB-231 cells when compared to non-tumor breast epithelial MCF10A cells. Likewise, PtDPhPzTn produced moderate S phase arrest and greatly impaired the migration ability of MDA-MB-231 cells. Most importantly, the co-stimulation of TNBC cells with PtDPhPzTn and melatonin substantially enhanced apoptosis and markedly improved the anti-migratory action compared to PtDPhPzTn alone. Altogether, our findings provide evidence that PtDPhPzTn and melatonin could be potentially applied to breast cancer treatment as powerful synergistic agents.